Neuropilin-2 Is Associated With Increased Hepatoblastoma Cell Viability and Motility - Eloranta, Katja; Nousiainen, Ruth; Cairo, Stefano; Pakarinen, Mikko P.; Wilson, David B.; Pihlajoki, Marjut; Heikinheimo, Markku (Frontiers in Pediatrics, 2021)
The neuropilins NRP1 and NRP2 are multifunctional glycoproteins that have been implicated in several cancer-related processes including cell survival, migration, and invasion in various tumor types. Here, we examine the role of neuropilins in hepatoblastoma (HB), the most common pediatric liver malignancy. Using a combination of immunohistochemistry, RNA analysis and western blotting, we observed high level expression of NRP1 and NRP2 in 19 of 20 HB specimens and in a majority of human HB cell lines (HUH6 and five cell lines established from patient-derived xenografts) studied but not in normal hepatocytes. Silencing of NRP2 expression in HUH6 and HB-282 HB cells resulted in decreased cell viability, impaired cytoskeleton remodeling, and reduced cell motility, suggesting that NRP2 contributes to the malignant phenotype. We propose that neuropilins warrant further investigation as biomarkers of HB and potential therapeutic targets.